Histórias invisibilizadas na terapia ocupacional: contribuições das mulheres negras na construção da profissão - Souza, Roberta dos Santos (Universidade Federal de São Carlos, 2025)
The research aimed to seek out, identify, and write about the life stories and contributions of self-identified Black Brazilian occupational therapists who graduated between 1958 and 2000. The investigative process included the analysis of historical documents, the review of articles and publications aligned with ethnic-racial themes, the conduction of interviews, among other sources that enabled the construction of a broad overview of the history of the Black Movement, Black women in science, and their participation in Occupational Therapy. Following multiple paths to identify the collaborators, nine escrevivências (lived and narrated experiences) of Black occupational therapists were gathered: Maria Bernardete da Silva Roque de Faria, Dalila Ribeiro Alves Vilella, Eliana Maria de Moraes, Marta Soares, Haydée Monteiro, Vanilza Rodrigues dos Santos, Márcia Cabral Costa, Rita de Cássia Barcellos Bittencourt, and Gilma Corrêa Coutinho. The contributions of Black occupational therapists to the construction and development of Occupational Therapy in Brazil are marked by pioneering efforts, ethical-political commitment, dedication, and the production of knowledge across various areas of practice, both professional and academic. Were pioneers in the expansion and implementation of Occupational Therapy courses in the states of Rio de Janeiro and Espírito Santo; in the creation of the Atelier Gaia (RJ); and in their work as consultants and project coordinators in collaboration with major Brazilian companies, expanding the professional scope of the field. In the realm of research and theoretical production, their highlights include participation in the Grupo de Estudos Profundos de Terapia Ocupacional (GEs.TO), with deep engagement in the theories of Rui Chamone and related publications. In teaching, they have led research lines such as AAAfroNTO and LAB Isè, helping to consolidate Black and intersectional epistemologies within Occupational Therapy. Their work also contributed to the consolidation and expansion of physical rehabilitation in Espírito Santo; to community-based practices focused on quilombola communities and the fight against racial inequalities, including participation in hetero-identification committees as mechanisms for ensuring affirmative action policies. Within Brazil’s Unified Health System (SUS), they have stood out in the field of mental health, working in substitute services and community- and territory-based care systems, with practices aimed at empowering individuals, ensuring rights, and strengthening the protagonism of socially vulnerable groups. The recognition of these escrevivências is essential for advancing a Brazilian Occupational Therapy that is critical, plural, anti-racist, and committed to social transformation
Invisible stories in occupational therapy: contributions of black women in the construction of the profession
Keywords: Mulheres negras; Terapia ocupacional; Escrevivências; Contribuições; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL